2014
DOI: 10.1371/journal.pone.0094503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel G2073A Mutation in 23S rRNA in Amphenicol-Selected Mutants of Campylobacter jejuni

Abstract: ObjectivesThis study was conducted to examine the development and molecular mechanisms of amphenicol resistance in Campylobacter jejuni by using in vitro selection with chloramphenicol and florfenicol. The impact of the resistance development on growth rates was also determined using in vitro culture.MethodsChloramphenicol and florfenicol were used as selection agents to perform in vitro stepwise selection. Mutants resistant to the selective agents were obtained from the selection process. The mutant strains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
10
1
Order By: Relevance
“…In our study, resistance to CHL was consistently the most difficult to obtain. Although this finding is in apparent disagreement with the observed 50% of persistent bacteraemia after CHL treatments 21 , it might be related to changes at the fitness level as has been observed in the presence of specific 23S rRNA gene point mutations in other microorganisms 23 24 25 .…”
Section: Discussioncontrasting
confidence: 55%
“…In our study, resistance to CHL was consistently the most difficult to obtain. Although this finding is in apparent disagreement with the observed 50% of persistent bacteraemia after CHL treatments 21 , it might be related to changes at the fitness level as has been observed in the presence of specific 23S rRNA gene point mutations in other microorganisms 23 24 25 .…”
Section: Discussioncontrasting
confidence: 55%
“…More crucial are mutations and/or deletions of ribosomal proteins, which are usually encoded by single gene copies. However, mutations in ribosomal proteins causing CAM-resistance have been identified only in a few cases so far [ 35 , 36 ]. Because interactions of CAM with ribosomal proteins have not been detected by crystallographic analyses [ 18 , 20 ], such resistance is suspected to arise indirectly, probably by induced conformational changes in rRNA.…”
Section: Bacterial Survival Strategies To Combat Cam Activitymentioning
confidence: 99%
“…It has been found that combination of both ribosomal protein and rRNA mutations lead to increased resistance; e.g. G-to-A nucleotide change at position 2073 (2058, E. coli numbering) in all three copies of the 23S rRNA gene in combination with G14D modification in ribosomal protein L4 confers CAM resistance in Campylobacter jejuni [ 36 ]. Nevertheless, such mutations are often accompanied by fitness cost and consequently are not extensively spread.…”
Section: Bacterial Survival Strategies To Combat Cam Activitymentioning
confidence: 99%
“…In our previous work, a point mutation, G2073A, was identified in 23 S rRNA in CAP-selected mutants of C. jejuni 19 . However, further study was needed to investigate whether this point mutation alone was sufficient to confer high-level resistance to CAP in the C. jejuni mutants.…”
Section: Introductionmentioning
confidence: 97%